Ljudmila & Anatolij - Bergdahl, Gunnar (Sweden; FantomFilm Produktion, 2006)
A film about love, death, the pain of those who have survived in the shadow of the Chernobyl disaster. A constant struggle between mother and son, memories and hopes, past and present.
Verzio Film Festival Submission
Keywords: Documentary films